Envelhecimento e desenvolvimento em assentamento rural do extremo sul paraense: o caso do assentamento Agropecus I. - Parrilha, Vinicius Alves (Universidade Federal do Tocantins, 2023)
In this work, we propose to analyze to what extent the production of the rural space of the Agropecus I Settlement, located in the municipality of Santa Maria das Barreiras, in the extreme south of Pará, influences the quality of life of the elderly. The research has a quantitative and qualitative approach, with an exploratory nature. Questionnaires were applied to 80 seniors among the 100 residing in the settlement and of which only one was selected to be interviewed. In the results, the socioeconomic and educational surveys of the 80 elderly respondents show that 43 are male and 37 are female, 66.3% have a partner, which may have an influence on their quality of life. As for the number of children, only 2.50% of respondents do not have children and 97.5% have between 1 and 10 children. Regarding professional life, 93.80% work in farming. Already 77% of the elderly receive 01 minimum wage, and often they contribute to the expenses of the family group. The prevalence of the level of education of the elderly is concentrated in elementary school (60%), while the degree of illiteracy among the elderly respondents reaches 31.3%. Regarding the respondents' health aspects and lifestyle habits, 71.30% consider themselves healthy, even when 64.80% of them use medication because of some underlying disease. Only 2.2% of the elderly have a private health plan, and most of them depend on the public services of the Unified Health System (SUS). From the results obtained, we can say that there is a need to improve the biopsychosocial model in public health, relevant to the elderly, emphasizing the need to consider the particularities of this fragile population in the face of the aging process.